Enhancing Fraction Learning: The Effectiveness of a Specialized Textbook for Slow Learners in Elementary Schools - Tri Murdiyanto; Anny Sovia; Dwi Antari Wijayanti (Institut Agama Islam Hidayatullah Batam, 2025)
This study aims to describe the effectiveness of a fraction textbook for slow‐learner students in elementary schools. The research design employed was a one-group pretest–posttest design. The sample consisted of slow‐learner students, and the learning material used in this study was fractions. Research data were obtained through pretests and posttests, and the pretest–posttest analysis was conducted using the N-Gain calculation. The results show that the learning outcomes of slow‐learner students (N-Gain) fall into the medium category. Based on these findings, the fraction textbook is effective in improving slow‐learner students’ conceptual understanding and implies that similar textbooks may serve as alternative learning resources to support fraction learning for slow‐learner students.